Informality Traps - Masatlioglu, Yusufcan; Rigolini, Jamele (2012)
Despite large deregulation efforts, informal economic activity still represents a large share of GDP in many developing countries. In this paper we look at incentives to reduce informal activity when capitalists in the formal sector regulate entry. We consider a dual economy with a formal sector employing educated workers and an informal sector with unskilled workers. We show that high costs of education make labor migration and profits in the formal sector an increasing function of its size. Therefore, incentives to allow capital to be reallocated to the formal sector increase with the size of the formal economy, and unless the formal sector has reached a "critical mass" countries remain in a highly informal equilibrium. We conclude by reviewing policies that can push countries with large informal economies towards formalization.